JIR2TA: Joint Invocation of Resource-Based Thresholding and Trust-Oriented Authentication in mobile adhoc network - Khan, Burhan Ul Islam; Zulkurnain, Nurul Fariza; Olanrewaju, Rashidah Funke; Nissar, Gousia; Baba, Asifa Mehraj; Lone, Sajad Ahmad (Springer, Cham, 2017)
The demands of a higher degree of security level for the mobile ad-hoc network are yet to meet the best solution. Owing to the dynamic topology and decentralization issue, the mobile node suffers from a consistent security problem during communication stage. This paper has reviewed the existing system towards secure routing in mobile ad-hoc network and explored that there are still a lot of scopes to enhance the security level. This paper presents a non-cryptographic technique called as JIR2TA or Joint Invocation of Resource-based Thresholding and Trust-oriented Authentication using resource and trust factor to intensify the routing policies for strengthening the authentication process of a mobile node. The outcome of the study shows better packet delivery ratio, computational time, throughput, and end-to-end delay in contrast to existing secure routing technique.